Pendampingan Penulisan Karya Ilmiah bagi Guru SMP Nusantara Sukolilo Kecamatan Sukodadi - Imam Syafi'i; Sofia Tri Septiawati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Scientific writing competence remains a significant challenge for teachers in fulfilling continuous professional development and academic publication requirements. This community service program aimed to improve teachers’ scientific writing competencies at SMP Nusantara Sukolilo, Sukodadi District, Lamongan Regency, through a participatory Action Learning approach involving workshops, intensive one-on-one coaching, and evaluation activities. Data were collected using assessments, observations, interviews, self-assessment rubrics, and evaluations of manuscript drafts. The results demonstrated improvements in teachers’ scientific writing competencies, including academic writing skills, reference searching, paraphrasing, citation practices, digital reference management, and the quality of article drafts in terms of problem formulation, academic argumentation, manuscript structure, and referencing consistency. The mentoring process also enhanced writing motivation, academic self-confidence, publication readiness, and reduced writing anxiety among participants. The program contributed to the development of a supportive academic culture and collaborative writing practices, indicating its effectiveness in strengthening teacher professionalism and educational quality improvement.